Polymorphism of the leptin gene in buffalo breed groups from eastern Amazon - Silva, Lorena Keyse; Barbosa, Elizabeth Machado; Silva, Sandra Cristina Becker; Campelo, José Elivalto Guimarães; Gonçalves, Evonnildo Costa; Silva, Caio Santos; Marques, José Ribamar Felipe; Silva Filho, Ednaldo (Veterinaria Italiana, 2021)
The objective of this work was to characterize genetically some buffalo herds raised in Varzea (VA) and Terra-Firme (upland) (TF) ecosystems through polymorphism of the intron 2 of the leptin gene ( LEP-1620). Two hundred seventy-nine animals from four distinct populations were evaluated using the PCR-RFLP method for LEP-1620 polymorphism (SNP) of the leptin gene with restriction enzyme BsaAI. The animal samples were sorted into 4 groups, according to their breed and environmental origin: Mediterranean TF, Murrah TF, Mediterranean VA and Crossbreed VA. Two alleles (A and G) were detected and their frequencies were analyzed. Allele A frequency ranged from 0.395 (Mediterranean TF) to 0.850 (Murrah TF), with AA genotype ranged from 0.114 (Murrah TF) to 0.700 (Mediterranean TF). The observed and expected heterozygosities ranged from 0.268 (Mediterranean TF) to 0.562 (Murrah TF), and 0.255 (Mediterranean TF) to 0.478 (Murrah TF), respectively. The Hardy-Weinberg probabilities were greater than 0.05. The Crossbred herd in Varzea was the only population with significant inbreeding and the Shannon index ranged between 0.423 (Mediterranean TF) and 0.671 (Murrah TF).